Mandatory Social Distancing for Covid-19 Outbreak and Its Economic Consequences in West Sumatera - Indonesia - Ridwan, Endrizal; Novianda, Besti (UI Scholars Hub, 2021)
The Governor of West Sumatra Province of Indonesia imposed a mandatory social distancing (PSBB) to slow down the Covid-19 outbreak from 22 April to 7 June 2020. The cons argued that PSBB was ineffective because of the impossibility to limit people’s movements. The pros, on the other hand, viewed PSBB as a training facility to increase people’s awareness about the pandemic. Our research aims at evaluating the effectiveness of PSBB by using the Kermack-McKendrick SIR pandemic model and the NLSUR non-linear least square estimation. Using daily data published by the Covid-19 task force, we found that PSBB had a positive impact on flattening the curve. Assuming that vulnerable people were around 30% of the population, PSBB has reduced the rate of spread of Covid-19 from around 2 persons to less than 1 person for every infected. We also found that the economic consequences of PSBB on commodities varied by their demand and supply characteristics. We, therefore, suggest that policy interventions related to price control and subsidy should consider these characteristics. For future research, as data more available, the effect of PSBB on broader economic variables such as poverty and growth in the province needs to be examined.